2017
DOI: 10.1093/sleep/zsx188
|View full text |Cite
|
Sign up to set email alerts
|

An Ambulatory Polysomnography Study of the Post-traumatic Nightmares of Post-traumatic Stress Disorder

Abstract: Post-traumatic nightmares of PTSD occur in both REM and non-REM sleep and are commonly associated with other sleep disturbances. These findings have important treatment implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 22 publications
0
42
1
1
Order By: Relevance
“…Such dreams often lead to awakening, in which case they are defined as nightmares. Nightmares are characterized by autonomic arousal, and the nightmares that occur in PTSD, which may emerge from non-REM sleep, as well as REM sleep, is associated with leg movements and/or respiratory events (Phelps et al, 2018). Nightmares are highly deleterious in PTSD, reducing the quality of life (El-Solh, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Such dreams often lead to awakening, in which case they are defined as nightmares. Nightmares are characterized by autonomic arousal, and the nightmares that occur in PTSD, which may emerge from non-REM sleep, as well as REM sleep, is associated with leg movements and/or respiratory events (Phelps et al, 2018). Nightmares are highly deleterious in PTSD, reducing the quality of life (El-Solh, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in autonomic activation in the presence of nightmares was even more pronounced when nightmares were compared against neutral dreams within the group of nightmare sufferers. A recent study in PTSD patients found no increase in heart rate within REM periods while experiencing nightmares (Phelps et al, ), but they neither included REM periods of a control group nor compared these REM periods with REM periods without nightmares. Furthermore, investigation of heart rate offers no insight into the pattern of autonomic arousal in terms of sympathetic and parasympathetic influences or differences.…”
Section: Discussionmentioning
confidence: 99%
“… 20 These changes are associated with respiratory or leg movement events and increase in heart rate on awakening. 21 Nonetheless, PSG may be warranted when obstructive sleep apnea is suspected as improvement in sleep quality and nightmares frequency has been reported after continuous positive airway pressure treatment. 22 …”
Section: Approach To Managementmentioning
confidence: 99%